Method and system for reducing adhesive strength and associated pull-out stress

By applying the first and second adhesives of different adhesive strengths on the bonding area, forming an adhesive bonding layer with low pull-off stress, the design and safety issues when removing adhesive bonding substrates in the prior art are solved, and a safer and more reliable separation process is achieved.

CN119899406APending Publication Date: 2025-04-29LORD CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510015052.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2019-07-31
Filing Date
2020-07-31
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

The prior art often requires the use of solvents, heat and/or high mechanical forces when removing adhesively bonded substrates, resulting in design limitations and safety issues, especially in battery modules and semiconductor applications, which are prone to damage and performance degradation.

Method used

By applying the first adhesive and the second adhesive on the bonding region, the adhesive strength of the second adhesive is lower than that of the first adhesive, forming an adhesive bonding layer containing both adhesives, reducing the pull-off stress, and reducing the adhesive strength by partial curing or temperature treatment.

Benefits of technology

The pull-off stress during the adhesively bonded substrate separation is effectively reduced by at least 20% to 80%, and the method is environmentally friendly, does not change the component design and minimizes changes in the adhesive formulation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119899406A_ABST
    Figure CN119899406A_ABST
Patent Text Reader

Abstract

The invention relates to a method and a system for reducing adhesive strength and related pull-out stress, and particularly discloses a method and a system for adhesively bonding a first substrate to a second substrate to reduce pull-out stress in a separation process of the first substrate and the second substrate. Comprising applying a first adhesive to a first bonding area of a bonding area of a first substrate, applying a second adhesive to a second bonding area of the bonding area of the first substrate, the adhesive strength of the second adhesive being lower than the adhesive strength of the first adhesive, pressing the first substrate and the second substrate against each other to form an adhesive bonding layer, and curing the first adhesive and the second adhesive for a predetermined period of time to form a cured adhesive bond layer between the first substrate and the second substrate.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This patent application is a divisional application of the patent application with application number 2020800549099, application date July 31, 2020, and invention name “Method and system for reducing bond strength and associated pull-off stress”.

[0002] CROSS-REFERENCE TO RELATED APPLICATIONS

[0003] This application claims the benefit of U.S. Provisional Patent Application No.

[0004] 62 / 880,701, the entire contents of which are incorporated herein by reference. Technical Field

[0005] The subject matter disclosed herein relates to methods and systems for reducing pull-off stress of adhesively bonded substrates. Background Art

[0006] It is usually necessary to use solvents, heat and / or large mechanical forces to remove adhesively bonded substrates. However, due to design limitations (e.g., inaccessible bonding layers) and / or safety considerations (e.g., physical deformation and / or damage to battery assemblies and / or battery cells within such battery assemblies), certain applications such as battery assemblies in electric vehicles do not allow the use of such methods. In fact, it is known that currently used techniques for removing adhesives from the surfaces of battery assemblies can irreversibly damage such battery assemblies in at least some cases. In the case of semiconductor applications, adhesives or thermal interface materials prevent the repair of components (e.g., silicon chips or microprocessors) because the high bonding strength of the adhesive can easily cause damage. Moreover, due to the different thermal expansion coefficients between the adhesive / TIM and the substrate, such adhesives generally lack the low modulus required to absorb stress and reduce part warpage. In addition, the performance requirements of certain applications require the use of toxic adhesives, such as traditional isocyanate-containing urethane adhesives. The limited serviceability / reworkability, performance and / or toxicity of such adhesively bonded substrates (e.g., typically used in battery assemblies) clearly demonstrates the urgent need for a safe and practical method of reducing the pull-off stresses induced during separation of adhesively bonded surfaces. Summary of the invention

[0007] The subject matter of the present disclosure includes a method that reduces the pull-off stress (e.g., the stress caused during the separation of two adhesively bonded substrates, which is directly related to the bond strength) by at least 20% relative to conventional known methods, while also passing an environmentally friendly cycle, not introducing any changes to the design of the component, and minimizing any possible changes in the adhesive formulation. In some embodiments, the method is capable of reducing the pull-off stress during the separation of two adhesively bonded substrates by (e.g.) at least 25%, at least 50%, at least 75%, or more than 80%. In addition, the method can be carried out using existing industrial facilities.

[0008] In an exemplary embodiment, a method for adhesively bonding a first substrate to a second substrate to reduce pull-off stress during separation of the first substrate and the second substrate is provided, the method comprising: applying a first adhesive to a first bonding area of ​​a bonding area of ​​the first substrate; applying a second adhesive to a second bonding area of ​​the bonding area of ​​the first substrate, the bonding strength of the second adhesive being lower than the bonding strength of the first adhesive; pressing the first substrate against the second substrate; and forming an adhesive bonding layer comprising the first adhesive and the second adhesive between the first substrate and the second substrate.

[0009] In some embodiments, the adhesive bonding layer is formed by at least partially curing the first adhesive and / or the second adhesive for a predetermined period of time.

[0010] In some embodiments of the method, the first bonding area of ​​the bonding area is the perimeter of the bonding area; and the second bonding area of ​​the bonding area is located within and defined by the perimeter formed by the first bonding area, such that the second adhesive at least partially fills the volume within the perimeter.

[0011] In some embodiments of the method, the second adhesive completely fills the volume within the second bonding area between the first substrate and the second substrate.

[0012] In some embodiments of the method, the first adhesive forms a continuous and uninterrupted layer around the perimeter of the bonding area.

[0013] In some embodiments of the method, the second bonding area of ​​the bonding area is a perimeter of the bonding area; and the first bonding area of ​​the bonding area is located within and bounded by the perimeter formed by the second bonding area such that the first adhesive at least partially fills the volume within the perimeter.

[0014] In some embodiments of the method, the first adhesive completely fills the volume within the first bonding area between the first substrate and the second substrate.

[0015] In some embodiments of the method, the second adhesive forms a continuous and uninterrupted layer around the perimeter of the bonding area.

[0016] In some embodiments of the method, the first adhesive and the second adhesive comprise the same two-component adhesive formulation; and the first adhesive has a different R:H ratio (resin to hardener) than the second adhesive.

[0017] In some embodiments of the method, the first binder has a degree of crosslinking that is greater than a degree of crosslinking of the second binder.

[0018] In some embodiments of the method, the second adhesive comprises an uncrosslinked material.

[0019] In some embodiments of the method, the greater degree of crosslinking is due to the different R:H ratios of the first binder and the second binder.

[0020] In some embodiments of the method, the R:H ratio of the first adhesive includes a relatively greater proportion of hardener than the R:H ratio of the second adhesive, and the R:H ratio of the second adhesive includes a relatively greater proportion of resin than the R:H ratio of the first adhesive.

[0021] In some embodiments of the method, at least one of the first adhesive and the second adhesive comprises at least one of a urethane, silicone, acrylic, and epoxy based material.

[0022] In some embodiments of the method, the first substrate comprises a heat source and the second substrate comprises a heat dissipation component; or the second substrate comprises a heat source and the first substrate comprises a heat dissipation component.

[0023] In some embodiments of the method, the heat source comprises a battery module and / or the heat dissipation component comprises a cooling plate.

[0024] In some embodiments of the method, the battery module is configured to provide power to an electric vehicle.

[0025] In some embodiments of the method, the heat source comprises a microprocessor and the heat dissipation component comprises a cover and / or a heat sink.

[0026] In some embodiments of the method, at least one of the first adhesive and the second adhesive comprises a thermally conductive filler resin composition.

[0027] In some embodiments of the method, at least one of the first adhesive and the second adhesive comprises a thermally conductive gap-filling adhesive.

[0028] In some embodiments, the first substrate is separated from the second substrate by destroying the adhesive bonding layer formed by the first adhesive and the second adhesive, wherein, due to the lower bonding strength of the second adhesive, the pull-off stress required to separate the first substrate and the second substrate is less than the pull-off stress required to separate the first substrate and the second substrate when the entire bonding area is covered by the first adhesive.

[0029] In some embodiments of the method, the bond strengths of the first adhesive and the second adhesive are related to (eg, directly related to) the pull-off stress required to separate the first substrate from the second substrate.

[0030] In some embodiments, the method includes irradiating at least a portion of the first adhesive with a light source having ultraviolet (UV) light to depolymerize at least a portion of the first adhesive exposed to the light source, such that the bonding strength of the first adhesive is reduced relative to the bonding strength of the first adhesive before exposure to the light source.

[0031] In some embodiments, the method includes exposing the first adhesive and the second adhesive to a temperature above a predetermined softening temperature to reduce the adhesive strength of at least the first adhesive after the first adhesive and / or the second adhesive have been cured, wherein one of the first substrate and the second substrate includes a heat source, and wherein the softening temperature is within an operating temperature range of the heat source.

[0032] In some embodiments, the adhesive in at least the first bonding area is an adhesive that is cured by irradiation with ultraviolet light.

[0033] In some embodiments of the method, the adhesive in the first bonding zone and the adhesive in the second bonding zone have comparable bond strengths, but when mixed together (e.g., in the area between the first bonding zone and the second bonding zone), the adhesives have lower or higher bond strengths.

[0034] In some embodiments of the method, the pull-off stress across the bond area is reduced by at least 50% relative to the pull-off stress with only adhesive alone applied in the same area (eg, across both the first bond area and the second bond area).

[0035] In some embodiments of the method, the adhesive in the first bonding region and the adhesive in the second bonding region are different one-component or two-component adhesives (eg, gap fillers).

[0036] In some embodiments of the method, the adhesive in the first bonding region and / or the second bonding region is configured to swell when a solvent is applied (eg, directly applied) thereto.

[0037] In another exemplary embodiment, a system is provided for adhesively bonding a first substrate to a second substrate to reduce pull-off stress during separation of the first substrate and the second substrate, the system comprising: a first adhesive applied to a first bonding area of ​​the bonding area of ​​the first substrate; and a second adhesive applied to a second bonding area of ​​the bonding area of ​​the first substrate, the bonding strength of the second adhesive being lower than the bonding strength of the first adhesive; wherein the system is configured such that the first substrate and the second substrate are pressed against each other to form an adhesive bonding layer, the adhesive bonding layer comprising the first adhesive and the second adhesive between the first substrate and the second substrate.

[0038] In some embodiments, the adhesive bond layer is formed by at least partially curing the first adhesive and / or the second adhesive for a predetermined period of time.

[0039] In some embodiments of the system, a first bonding zone of the bonding area is a perimeter of the bonding area; and a second bonding zone of the bonding area is located within and defined by the perimeter formed by the first bonding zone such that the second adhesive at least partially fills a volume within the perimeter.

[0040] In some embodiments of the system, the second adhesive completely fills the volume within the second bonding area between the first substrate and the second substrate.

[0041] In some embodiments of the system, the first adhesive forms a continuous and uninterrupted layer around the perimeter of the bonding area.

[0042] In some embodiments of the system, the second bonding area of ​​the bonding area is a perimeter of the bonding area; and the first bonding area of ​​the bonding area is located within and bounded by the perimeter formed by the second bonding area, such that the first adhesive at least partially fills the volume within the perimeter.

[0043] In some embodiments of the system, the first adhesive completely fills the volume within the first bonding region between the first substrate and the second substrate.

[0044] In some embodiments of the system, the second adhesive forms a continuous and uninterrupted layer around the perimeter of the bonding area.

[0045] In some embodiments of the system, the first adhesive and the second adhesive comprise the same two-component adhesive formulation; and the first adhesive has a different R:H ratio (resin to hardener) than the second adhesive.

[0046] In some embodiments of the system, the first binder has a degree of crosslinking that is greater than a degree of crosslinking of the second binder.

[0047] In some embodiments of the system, the second adhesive comprises an uncrosslinked material.

[0048] In some embodiments of the system, the greater degree of crosslinking is due to the different R:H ratios of the first binder and the second binder.

[0049] In some embodiments of the system, the R:H ratio of the first adhesive includes a relatively greater proportion of hardener than the R:H ratio of the second adhesive, and the R:H ratio of the second adhesive includes a relatively greater proportion of resin than the R:H ratio of the first adhesive.

[0050] In some embodiments of the system, at least one of the first adhesive and the second adhesive comprises at least one of a urethane, silicone, acrylic, and epoxy based material.

[0051] In some embodiments of the system, the first substrate comprises a heat source and the second substrate comprises a heat dissipation component; or the second substrate comprises a heat source and the first substrate comprises a heat dissipation component.

[0052] In some embodiments of the system, the heat source includes a battery module and / or the heat dissipation component includes a cooling plate.

[0053] In some embodiments of the system, the battery module is configured to provide power to an electric vehicle.

[0054] In some embodiments of the system, the heat source includes a microprocessor and the heat dissipation component includes a cover and / or a heat sink.

[0055] In some embodiments of the system, at least one of the first adhesive and the second adhesive comprises a thermally conductive filler resin composition.

[0056] In some embodiments of the system, at least one of the first adhesive and the second adhesive comprises a thermally conductive gap-filling adhesive.

[0057] In some embodiments of the system, the system is configured to separate the first substrate from the second substrate by destroying the adhesive bonding layer formed by the first adhesive and the second adhesive; and due to the lower bonding strength of the second adhesive, the pull-off stress required to separate the first substrate and the second substrate is less than the pull-off stress required to separate the first substrate and the second substrate when the entire bonding area is covered by the first adhesive.

[0058] In some embodiments of the system, the bond strength of the first adhesive and the second adhesive is related to a pull-off stress required to separate the first substrate from the second substrate.

[0059] In some embodiments of the system, at least a portion of the first adhesive is configured such that, when at least a portion of the first adhesive is irradiated with a light source having ultraviolet (UV) light to depolymerize at least a portion of the first adhesive exposed to the light source, the bonding strength of the first adhesive is reduced relative to the bonding strength before the first adhesive was exposed to the light source.

[0060] In some embodiments of the system, the system is configured to reduce at least the adhesive strength of the first adhesive when exposed to a temperature above a predetermined softening temperature after the first adhesive and / or the second adhesive has been cured; one of the first substrate and the second substrate includes a heat source; and the softening temperature is within an operating temperature range of the heat source.

[0061] In some embodiments of the system, the adhesive in the first bonding zone and the adhesive in the second bonding zone have comparable bond strengths, but when mixed together (e.g., in the area between the first bonding zone and the second bonding zone), the adhesives have lower or higher bond strengths.

[0062] In some embodiments of the system, the pull-off stress across the bond area is reduced by at least 50% relative to the pull-off stress with only adhesive alone applied in the same area (eg, across both the first bond area and the second bond area).

[0063] In some embodiments of the system, the adhesive in the first bonding region and the adhesive in the second bonding region are different one-component or two-component adhesives (eg, gap fillers).

[0064] In some embodiments of the system, the adhesive in the first bonding region and / or the second bonding region is configured to swell when a solvent is applied (eg, directly applied) thereto.

[0065] In another exemplary embodiment, a method for adhesively bonding a first substrate to a second substrate to reduce pull-off stress during separation of the first substrate and the second substrate is provided, the method comprising: applying a first adhesive to a bonding area of ​​the first substrate; applying a second adhesive to a bonding area of ​​the first substrate; pressing the first substrate against the second substrate; and forming an adhesive bonding layer including the first adhesive and the second adhesive between the first substrate and the second substrate, wherein the bonding strength of the adhesive bonding layer is lower than the bonding strength of an adhesive bonding layer formed entirely of only the first adhesive or only the second adhesive.

[0066] In some embodiments of the method, the first adhesive and the second adhesive have substantially similar bond strengths.

[0067] In some embodiments of the method, the first adhesive and the second adhesive are at least partially mixed together when the first substrate is pressed against the second substrate.

[0068] In some embodiments, the method includes separating the first substrate from the second substrate by destroying an adhesive bonding layer formed by a first adhesive and a second adhesive, wherein because the adhesive bonding layer has a lower adhesive strength than an adhesive bonding layer formed entirely of only the first adhesive or only the second adhesive, a pull-off stress required to separate the first substrate and the second substrate is less than a pull-off stress required to separate the first substrate and the second substrate if the entire bonding area is covered by only the first adhesive or only the second adhesive.

[0069] In another exemplary embodiment, a system is provided for adhesively bonding a first substrate to a second substrate to reduce pull-off stress during separation of the first substrate and the second substrate, the system comprising: a first adhesive applied to a bonding area of ​​the first substrate; and a second adhesive applied to a bonding area of ​​the first substrate; wherein the system is configured such that when the first substrate and the second substrate are pressed against each other, an adhesive bonding layer comprising the first adhesive and the second adhesive is formed between the first substrate and the second substrate; and wherein the bonding strength of the adhesive bonding layer is lower than the bonding strength of an adhesive bonding layer formed entirely of only the first adhesive or only the second adhesive.

[0070] In some embodiments of the system, the first adhesive and the second adhesive have substantially similar adhesive strengths.

[0071] In some embodiments of the system, the first adhesive and the second adhesive are at least partially mixed together when the first substrate is pressed against the second substrate.

[0072] In some embodiments of the system, the system is configured to separate the first substrate from the second substrate by destroying the adhesive bonding layer formed by the first adhesive and the second adhesive; and because the adhesive strength of the adhesive bonding layer is lower than the adhesive strength of the adhesive bonding layer formed entirely by only the first adhesive or only by the second adhesive, the pull-off stress required to separate the first substrate and the second substrate is less than the pull-off stress required to separate the first substrate and the second substrate if the entire bonding area is covered by only the first adhesive or only by the second adhesive.

[0073] As used herein, the term "adhesive" may be used to refer to a cross-linked or uncross-linked material used to mechanically and / or thermally join (e.g., connect, such as in direct contact with each substrate) at least two substrates. Thus, any and all "adhesives" referred to herein may include, but are not necessarily limited to, any adhesive, compound, and / or material; adhesive, compound, and / or material; thermosetting agent, compound, and / or material; adhesive, compound, material, and / or composite material; thermoplastic agent, compound, and / or material; hot melt adhesive, compound, and / or material; mating agent, compound, and / or material; structural adhesive, compound, and / or material; sealant, compound, and / or material; adhesive film; interface material; interface pad; and grease. The above list also includes thermally conductive versions of each substance. As used herein, the term "thermally conductive" refers to a material having a thermal conductivity of at least 1.0 Watt per meter-Kelvin (W / mK), and preferably at least 2.0 W / mK, at least 3.0 W / mK, at least 4.0 W / mK, at least 5.0 W / mK, or at least 6.0 W / mK, for example but not limited thereto. In addition, the term "thermally conductive" does not include materials that one of ordinary skill in the art would determine to be thermal insulators (e.g., typically used to maintain temperature gradients by inhibiting heat transfer).

[0074] As used herein, the terms "resin" and "hardener" are used to refer to subcomponents of a two-component system (eg, a two-component material or compound, which may be an adhesive), wherein mixing of the subcomponents causes the two-component system to cure.

[0075] As used herein, the term gap filler is intended to be an adhesive that fills a gap between two or more substrates to be bonded together and also forms an adhesive bond between the two or more substrates, however, in some cases, the terms "gap filler" and "adhesive" may be used interchangeably herein.

[0076] Compared to conventional, non-patterned (e.g., having a continuous R:H ratio in a cross-section of the adhesive bonding layer) thermally conductive adhesives, the exemplary methods and systems disclosed herein significantly reduce damage to battery components during maintenance while also enabling reliable thermal performance during use. Although described herein with silicone-based gap fillers, the exemplary methods disclosed herein are applicable to other gap filling chemistries, such as urethanes (polyols / isocyanates), epoxies, etc. In one embodiment of the present invention, the method disclosed herein includes using any two-component adhesive as the first adhesive and the second adhesive by using different proportions of the two components for an adhesive applied in a first bonding area of ​​the bonding area and an adhesive applied in a second bonding area of ​​the bonding area. BRIEF DESCRIPTION OF THE DRAWINGS

[0077] Figure 1is a perspective view of an adhesive applied to a surface of a T-bar structure.

[0078] Figure 2 is applied in an exemplary pattern Figure 1 Bottom view of the adhesive on the surface of the T-bar structure.

[0079] Figure 3 is a schematic diagram of a bonding area in which a first bonding area and a second bonding area are defined.

[0080] Figure 4 is a perspective view of the test apparatus, where Figure 1 The T-bar structure shown is bonded to the surface of a second T-bar structure to measure a pull-off force applied to the T-bar structure during separation of the first T-bar structure and the second T-bar structure.

[0081] Figure 5 is a table showing the results of empirical testing used to measure the pull-off stress of different formulations and / or arrangements of adhesive materials.

[0082] FIG. 6A to FIG. 6D Shown in Figure 4 Remnants of different formulations and / or arrangements of adhesive material at the bonding surface between T-bar structures are shown.

[0083] Figure 7 A perspective view of an exemplary embodiment of a heating device configured to cyclically heat and cool an adhesive material is shown.

[0084] Figure 8 Shown in Figure 7 Residue of adhesive material after 1000 heating / cooling cycles in the heating apparatus shown. DETAILED DESCRIPTION

[0085] In a first exemplary embodiment disclosed herein, a method for forming an adhesive bond between at least two substrates is provided, which reduces the pull-off stress (e.g., defined as the removal force divided by the surface area of ​​the bond) required to separate the substrates when the substrates are separated from each other. The method includes adhesively bonding a plurality of substrates on a bonding area, in which a first bonding area has a first adhesive different from a second adhesive applied to a second bonding area, and the bonding strength of the second adhesive in the second bonding area is lower than the bonding strength of the first adhesive in the first bonding area. As used herein, the bonding strength is related to (e.g., directly related to) the pull-off force required to separate the adhesively bonded substrates, which means that an adhesive with increased bonding strength will require a greater pull-off force to separate the adhesively bonded substrates compared to the pull-off force required to separate the substrates bonded using an adhesive with low bonding strength. In some embodiments, the first adhesive and the second adhesive contain the same components, but these components are mixed in different proportions. In some embodiments, the first adhesive and the second adhesive are different adhesives and have different chemical and / or molecular compositions.

[0086] The first adhesive is applied (e.g., directly) to the first bonding area and / or the first bonding area of ​​the bonding area of ​​the first substrate. The second adhesive is applied (e.g., directly) to the second bonding area and / or the second bonding area of ​​the bonding area of ​​the first substrate. The first bonding area and the second bonding area together can be equal to or less than the total surface area of ​​the bonding area of ​​the first substrate and / or the second substrate. In some embodiments, before the second adhesive is applied to the second bonding area, the first adhesive is applied to the first bonding area. In some embodiments, before the first adhesive is applied to the first bonding area, the second adhesive is applied to the second bonding area.

[0087] The second adhesive, while having a lower adhesive strength than the first adhesive, provides sufficient adhesion to maintain contact between the substrates and also substantially fills (e.g., at least 75% or more, at least 80% or more, at least 90% or more, at least 95% or more, or at least 99% or more) that portion of the volume between the substrates corresponding to the second bonding area over which the second adhesive is applied. The combined adhesive strength of the first adhesive and the second adhesive provides sufficient adhesive strength to maintain an adhesive bond between the two substrates when the bonded substrates are subjected to mechanical and environmental influences (e.g., as input during use).

[0088] In some embodiments, the first adhesive and the second adhesive can be applied to different substrates such that (for example) the first adhesive is applied to the first bonding area and / or the first bonding area of ​​the first substrate or the second substrate, and the second adhesive is applied to the second bonding area and / or the second bonding area of ​​the second substrate or either of the first substrates to which the first adhesive is not applied.

[0089] In some embodiments, the first adhesive and the second adhesive comprise the same two-component adhesive formulation, but are mixed with different resin (R) and hardener (H) ratios. As used herein, the term "two-component adhesive formulation" refers to that the first adhesive and the second adhesive each use the same resin and the same hardener, but the R:H ratio of the first adhesive is different from the R:H ratio of the second adhesive. By using different R:H ratios in the first adhesive and the second adhesive, due to the different curing or crosslinking degrees provided by the interaction of the resin / hardener in the first adhesive and the second adhesive, the bonding strength of the first adhesive and the second adhesive is different. The bonding strength of the first adhesive and / or the second adhesive can be changed by changing the R:H ratio.

[0090] In some embodiments, the first adhesive and the second adhesive comprise substantially different adhesive formulations that are tailored to provide a predetermined bond strength based on the application. Thus, the first adhesive and the second adhesive may, for example, use different curable resins, hardeners, fillers, etc., or may contain different relative proportions of any curable resin, hardener, filler, etc. in each of the different adhesive formulations.

[0091] When applied to the first bonding area and the second bonding area between two substrates to be bonded respectively, the pattern of the first adhesive and the second adhesive can be different from those shown in this article, which does not deviate from the scope of the subject matter disclosed herein.In the exemplary embodiments shown in this article, the bonding area defines the perimeter around the bonding area, and the bonding area is the surface area of ​​the substrate to be bonded together, and the second bonding area is limited in the first bonding area (for example, concentrically in the first bonding area), to partially or substantially completely fill the volume defined in the perimeter formed by the first adhesive. The composite bonding strength of the adhesive bonding formed by the first adhesive and the second adhesive (for example, the total bonding strength of the adhesive bonding between the substrates) can be increased or reduced by applying relatively more or less first adhesive and the second adhesive (for example, by changing the relative ratio of the first bonding area and the second bonding area of ​​the bonding area). For example, the composite bonding strength can be increased by increasing the ratio of the first bonding area with the first adhesive applied thereon. The composite bonding strength can be reduced by reducing the ratio of the first bonding area with the first adhesive applied thereon. When the proportion of the first bonding area on which the first adhesive is applied increases to increase the bonding strength, the proportion of the second bonding area on which the second adhesive is applied decreases, or when the second adhesive does not completely fill the space defined within the perimeter formed by the first adhesive, the proportion of the second bonding area on which the second adhesive is applied can remain unchanged. When the proportion of the first bonding area on which the first adhesive is applied decreases to reduce the bonding strength, the proportion of the second bonding area on which the second adhesive is applied can remain unchanged or can increase to fill a larger proportion of the second bonding area defined within the perimeter formed by the first adhesive.

[0092] In another exemplary embodiment, the second bonding area defines a perimeter around the bonding area, which is the surface area of ​​the substrates to be bonded together, and the first bonding area is defined within the second bonding area (e.g., concentrically within the second bonding area) to partially or substantially completely fill the volume defined within the perimeter formed by the second adhesive (e.g., which has a lower bonding strength than the first adhesive). The composite bonding strength of the adhesive bond formed by the first adhesive and the second adhesive can be increased or decreased by applying relatively more or less of the first adhesive and the second adhesive (e.g., by changing the relative ratio of the first bonding area and the second bonding area of ​​the bonding area). For example, the composite bonding strength can be increased by increasing the proportion of the first bonding area (e.g., the inner part of the bonding area, within the perimeter formed by the second adhesive) on which the first adhesive is applied. The composite bonding strength can be reduced by reducing the proportion of the first bonding area (e.g., the inner part of the bonding area, within the perimeter formed by the second adhesive) on which the first adhesive is applied.

[0093] In some embodiments of the method, the first substrate includes a heat source (e.g., a battery assembly, a battery pack, etc.) and the second substrate includes a heat dissipation component (e.g., a cooling plate or other suitable heat dissipation structure), and a thermally conductive adhesive (e.g., a gap filler or other suitable thermal interface material) is required between the heat source and the heat dissipation component to transfer heat from the heat source to the heat dissipation component. In an exemplary embodiment, the first substrate includes a battery module, which is adhesively bonded to the second substrate including the cooling plate by a two-component thermally conductive (TC) gap filling adhesive material. Another exemplary embodiment may include a semiconductor application in which a microprocessor is adhered to a protective heat dissipation cover or a protective heat dissipation cover adhered to a heat dissipation component.

[0094] In some embodiments of the method, the adhesive applied to the first bonding area and the second bonding area can be selected to cause the adhesive applied to the second bonding area (e.g., within the perimeter formed by the adhesive applied to the first bonding area) to fail in a cohesive manner. In some embodiments, the adhesive applied to the second bonding area can be selected to fail in an adhesive manner.

[0095] In some embodiments, the method can achieve reduced stress (e.g., corresponding to a reduction in pull-off stress) upon removal or separation compared to conventional methods by (e.g., in a stepwise manner) changing the R:H ratio of the adhesive across the cross-section of the bonding area to produce a first bonding area comprising an adhesive having a well-crosslinked R:H ratio relative to a second bonding area comprising an adhesive having a relatively lightly crosslinked R:H ratio. When the first bonding area and the second bonding area have different bond strengths due to the change in the R:H ratio across the cross-section of the bonding area, the adhesive maintains its ability to transfer heat between the battery module and the cooling plate and prevents separation of the battery module and the cooling plate during conventional operation.

[0096] In some embodiments of the method, the adhesive can be a one-component or two-component adhesive, with different portions of the adhesive being cured differently due to the application of two different adhesive formulations within a first bonding zone and a second bonding zone of the bonding area, wherein one adhesive formulation provides a higher bond strength and / or stress and is applied to the first bonding zone, and the second adhesive formulation provides a lower bond strength and / or stress and is applied to the second bonding zone.

[0097] In some embodiments, the adhesive applied to the second bonding area comprises a phase change material or a thermally conductive gap pad.

[0098] In some embodiments, the method includes applying an adhesive-release agent to at least a portion of the bonding area (e.g., a second bonding area, as described elsewhere herein) of at least one substrate (e.g., a battery module and / or a cooling plate) prior to applying any adhesive to the substrate (e.g., to a portion of the bonding area to which the release agent has been or will be applied). Applying the release agent to at least the second bonding area of ​​the bonding area of ​​at least one substrate reduces the adhesive retention between the adhesive and the substrate, the substrate having the release agent applied to at least a portion of the bonding area, and / or the substrate having the release agent applied covering it. In some embodiments, the method includes applying the release agent by patterning the release agent to a portion of the bonding area of ​​the substrate (e.g., the second bonding portion), making the already reduced bonding force (e.g., relative to an adhesive bond without the release agent applied) even lower in that portion; thus, a reduced pull-off force and / or stress can be expected to form an area of ​​low pull-off stress within the bonding area. In some embodiments, the method includes selecting and applying an anti-adhesive agent to at least a portion of the bonding area (e.g., to a portion or all of the first bonding area and / or a portion or all of the second bonding area), wherein, depending on the chemical composition of the one or more adhesives that come into contact with the anti-adhesive agent and the chemical composition of the applied anti-adhesive agent, the anti-adhesive agent preferentially causes enhanced and / or impaired cross-linking of the applied adhesive within the portion of the bonding area to which the anti-adhesive agent is applied.

[0099] In some embodiments, the method includes applying a first adhesive in the form of a one-component or two-component adhesive formulation in a first bonding zone (e.g., around the perimeter of the bonding zone) of one of the two substrates to be bonded, the first adhesive providing high bond strength and / or stress, and requiring a correspondingly high pull-off force and / or stress to separate the substrates after the first adhesive has been cured. The method includes applying a second adhesive such as an uncured thermoplastic in a second bonding zone (e.g., within the perimeter formed by the first adhesive in the first bonding zone) of the bonding zone, the second adhesive providing lower bond strength and / or stress than that provided by the cured first adhesive; thus, requiring a correspondingly lower pull-off force and / or stress to separate the substrates than if the first adhesive were also applied to the portion of the bonding zone to which the second adhesive was applied.

[0100] In some embodiments, the first adhesive and the second adhesive are identical or different adhesives, for example, can be uncrosslinked (e.g., thermoplastics). According to such embodiments, for example, such uncrosslinked adhesives can be applied using heat or by applying a solvent. In some such embodiments, one or more solvent-based thermoplastics are applied (e.g., distributed) in the first bonding area and / or the second bonding area of ​​the bonding area of ​​the first substrate (e.g., a heat source, such as a battery module). In some embodiments, different solvent-based thermoplastics are applied to the first bonding area and the second bonding area. After one or more solvent-based thermoplastics are applied to the bonding area, one or more solvent-based thermoplastics are dried and the first substrate is positioned (e.g., by pressing and / or clamping) against the second substrate (e.g., a heat dissipation component, such as a cooling plate) so that one or more solvent-based thermoplastics are in contact (e.g., direct contact) with the second substrate. Once the one or more solvent-based thermoplastic materials are in contact with the second substrate, the one or more solvent-based thermoplastic materials are heated (e.g., by applying heat to the second substrate) such that the one or more solvent-based thermoplastic materials on the portions of the second substrate in contact with the one or more solvent-based thermoplastic materials are wetted (e.g., forming a conformal coating).

[0101] In some embodiments, the method includes applying a first adhesive in the form of a one-component or two-component adhesive formulation to a first bonding area of ​​the bonding area and / or covering it (e.g., around the perimeter of the bonding area) to provide high bonding strength and / or stress, and after the first adhesive has been cured, a correspondingly high pull-off force and / or stress is required to separate the substrates, and the high bonding strength and / or stress provided by the first adhesive is configured to reduce when the first adhesive is exposed to a temperature above a predetermined temperature threshold. The method also includes applying a second adhesive in the form of a lightly or uncrosslinked adhesive material to a second bonding area of ​​the bonding area and / or covering it (e.g., inside formed by the first bonding area of ​​the bonding area). Therefore, when exposed to a temperature above the predetermined temperature threshold, the first adhesive applied around the perimeter of the bonding area may have a significantly reduced (e.g., 50% or more, 75% or more) bonding strength, at least relative to the pull-off stress caused when the substrates are separated without preheating the first adhesive to above the predetermined temperature threshold, and this heat-induced reduction in bonding strength is conducive to further assisting the disintegration of the adhesive bonding layer. In some such embodiments, the predetermined temperature threshold is a temperature at which the bond strength of the first adhesive is significantly reduced (e.g., 50% or more, 75% or more) in the first bonding area of ​​the bonding area (e.g., around the perimeter of the bonding area), and the predetermined temperature threshold is lower than the upper temperature limit of the adhesively bonded components (e.g., in a battery module). In some embodiments, the bond strength of one or both adhesives can be reduced by changing the pH of the adhesive, applying a solvent, irradiating with light or sound, etc.

[0102] In some embodiments, the method includes applying a first adhesive in the form of a one-component or two-component adhesive formulation in the first bonding area of ​​the bonding area and / or covering it (e.g., around the perimeter of the bonding area) to provide high bonding strength and / or stress, and after the first adhesive is cured, a correspondingly high pull-off force and / or stress is required to separate the substrates. According to this embodiment, the first adhesive can be configured to undergo a depolymerization process when the exposed portion of the first bonding area (e.g., the external visible portion of the perimeter of the first adhesive around the bonding area) is directly subjected to ultraviolet (UV) light. As used herein, the term "directly subjected" can mean that the device for outputting UV light is arranged so that the UV light from the device is guided and incident on (e.g., irradiated and / or radiated) the exposed portion of the first adhesive in the first bonding area. Therefore, according to this exemplary method, the bonding strength of the first adhesive on at least a portion of the first bonding area of ​​the bonding area is significantly reduced (e.g., 50% or more, 75% or more) by UV-induced depolymerization, thereby facilitating further assisting the disintegration of the adhesive bonding layer during the substrate separation process. The exemplary embodiment further includes applying a second adhesive in the form of a relatively weakly cross-linked or uncross-linked adhesive material to at least the second bonding area (e.g., an interior area of ​​the bonding area formed within a perimeter defined by the first bonding area) such that the second adhesive provides a lower bond strength and / or stress and requires a correspondingly lower pull-off force and / or stress to separate the substrates at the adhesive bonding layer.

[0103] In another embodiment of the present invention, the method includes applying a single component UV curable adhesive on a first bonding area of ​​the bonding area, applying a second adhesive on a second bonding area of ​​the bonding area, pressing the substrates against each other to form an adhesive bond layer, and exposing the perimeter to UV light to polymerize the UV curable adhesive.

[0104] In some embodiments, the method includes applying a first adhesive in the form of a one-component or two-component adhesive formulation, the first adhesive being applied around the perimeter of the bonding area to provide high bond strength and / or stress, and requiring a correspondingly high pull-off force and / or stress to separate the substrates when the first adhesive is cured. According to this embodiment, a second adhesive in the form of a thermally conductive pre-cured gap pad is applied to at least a portion of the bonding surface within the perimeter formed by the first adhesive, such that the second adhesive provides a lower bond strength and / or stress, and a correspondingly lower pull-off force and / or stress is required to separate the substrates at the adhesive bond line.

[0105] According to the methods disclosed herein, the pull-off stress over the entire bonding area is reduced by at least 20% (e.g., 20% or more, 30% or more, 40% or more, 50% or more, 75% or more, 90% or more) compared to the pull-off stress required to separate the substrates at an adhesive bonding layer formed on the same bonding area but applied to a portion of the bonding area (in the methods described herein, the first adhesive and the second adhesive are applied as alternatives in the portion) in which the R:H ratio of the adhesive is the same as the R:H ratio of the first adhesive.

[0106] In some embodiments, by using the same adhesive in the first bonding area and the second bonding area but using different R:H ratios, a variable crosslink density from the outside to the inside of the bonding area and correspondingly variable bond strength is generated while still maintaining a highly thermally conductive bonding layer. It may be advantageous to use adhesives with the same basic chemical composition and compatible with each other in the first bonding area and the second bonding area because this can produce a favorable interaction at the interface between the first bonding area and the second bonding area (see, e.g. Figure 3 132 in ).

[0107] Figures 1 to 8 Various aspects of the test apparatus 100 and / or results used to validate the efficacy of the methods disclosed herein are shown. Figures 1 to 4 , an exemplary aspect of a test apparatus 100 is shown for measuring the tensile pull-off stress required to separate aluminum substrates (e.g., T-bar structures 110A, 110B) that are adhesively bonded together by thermally conductive adhesive gap fillers 130 in the exemplary embodiments disclosed herein. The aluminum substrates used in the exemplary embodiments disclosed herein correspond to structures found in battery module-cooling plate assemblies commonly found in many electric vehicle (EV) applications. Figures 1 to 4 When evaluating the efficacy of the methods disclosed herein using the test apparatus 100 shown in FIG. 1 , the ratio of resin to hardener (R:H ratio) in the adhesive gap filler is systematically varied in different regions of the adhesive bond area (see, e.g., Figure 3 ). As shown and used in the exemplary drawings, the term "perimeter" (Per) is used to indicate a first bonding area, while the term "center" is used to indicate a second bonding area bounded by the perimeter of the bonding area formed by the first bonding area.

[0108] exist Figures 1 to 4In a test apparatus of FIG. 1 , an adhesive is applied to a bonding area 134 on one of two T-bar structures 110A, 110B. In order to form a repeatable adhesive bonding layer of 1.0 mm, a spacer 140 having a thickness of 1.0 mm is disposed between the surfaces of each T-bar structure 110A, 110B, and the spacer 140 is disposed on opposite ends of the T-bar structures 110A, 110B (e.g., along the length direction of the T-bar structures 110A, 110B) to prevent the T-bar structures 110A, 110B from compressing the adhesive in the bonding area 134 to be thinner than 1.0 mm.

[0109] For the first exemplary evaluation presented herein, a two-component, 3.8 W / mK thermally conductive silicone gap filling adhesive 130 ( SC-1500, available from LORD Corporation) is applied within the bonding area generally indicated as 134 in the first bonding area 130A and / or the second bonding area 130B. The adhesive in the first bonding area 130A is mixed to have an R:H ratio of 1:1 and applied to one of the T-bar structures 110A, 110B (e.g., using a handheld dispenser), which creates the first bonding area 130A around the perimeter of the bonding area 134, such that the first bonding area 130A has a width of about 5 mm to 6 mm and a thickness of about 1 mm, as shown in FIG. Figure 2 As shown. In this article, for the first exemplary embodiment (for example, in Figure 5 6 ), substantially all (e.g., at least 90%, at least 95%, or at least 99%) of the volume defined by second bonding area 130B is either void or filled with an exemplary second adhesive having a different R:H ratio (e.g., 2:1 or 1:2).

[0110] In one exemplary sample, the SC-1500 completely filled the entire bonding area 134 at a thickness of about 1 mm to create a control bonding area. The data for this example is shown in Figure 5 The first column plotted in the column chart and the first row of data in the table of Figure 6. Figure 5 The second and third columns plotted in the bar graph of FIG. 6 and the second and third rows of data in FIG. 6 are respectively applied to the entire bonding area 134 with a thickness of about 1 mm. A control sample of SC-1500 containing only the resin (R) component or only the hardener (H) component. In another exemplary sample, Figure 5 As shown in the fourth column drawn in the bar graph of FIG. 6 and the data in the fourth row, the first bonding area 130A is filled with a 1:1 R:H ratio mixed and having a thickness of about 1 mm. SC-1500, while the volume between the T-bar structures 110A, 110B in the second bonding area 130B is left empty or filled with ambient air. Figure 5 As shown in the fifth column drawn in the bar graph of FIG. 6 and the fifth row of data, the first bonding area 130A is filled with a 1:1 R:H ratio mixed and having a thickness of about 1 mm. SC-1500, and the second bonding area 130B is filled with a mixture of 2:1 R:H ratio and a thickness of about 1 mm. SC-1500. In another exemplary sample, Figure 5 As shown in the sixth column drawn in the bar graph of FIG. 6 and the sixth row of data in FIG. 6 , the first bonding area 130A is filled with a 1:1 R:H ratio mixed and having a thickness of about 1 mm. SC-1500, and the second bonding area 130B is filled with a mixture of 1:2 R:H ratio and a thickness of about 1 mm. SC-1500.

[0111] As just described above, after a control of adhesive or only resin or only hardener is applied to a portion of the bonding area 134, the T-bar structure 110B to which no adhesive is applied is placed on the T-bar structure 110A to which one or more adhesives and / or resins or hardeners are applied, so that the T-bar structures 110A, 110B are substantially aligned with each other in the length and width directions, and the T-bar structures 110A, 110B are pressed together until the spacers 140 located at each longitudinal end of the bonding area 134 are in contact (e.g., in direct contact) with the surfaces of the T-bar structures 110A, 110B, so that a desired bonding layer thickness is formed by the one or more adhesives applied within the bonding area 134.

[0112] When the T-bar structures 110A, 110B are pressed together, any excess material (e.g., first adhesive, resin, and / or hardener) having a volume greater than the volume between the T-bar structures 110A, 110B in the bonding area 134 is squeezed out (e.g., pressed out) from the sides (e.g., in the width direction) of the volume defined by the bonding area 134. The test device 100 is then cured at approximately 100° C. (e.g., + / - 5° C. to account for differences in heating equipment, such as an oven, which is typically maintained within a tolerance range by thermostatic control) for 1 hour. After curing, the exposed perimeter of the first bonding area 130A is trimmed (e.g., using a razor blade) to remove any adhesive material that has squeezed out of the volume defining the adhesive bond layer, thereby producing a first bonding area 130A that has substantially similar (e.g., within 10%, within 5%, within 1%) outer dimensions to the bonding area 134 between the spacers 140 and defined by the width of the T-bar structures 110A, 110B, but allowing the adhesive within the first bonding area 130A to have smaller dimensions than the dimensions of the bonding area 134, such as at the corners thereof. Figure 4 shown.

[0113] Obtained as follows Figure 5 The pull-off stress data shown in FIG. 1 shows a test apparatus 100 positioned within a test frame and applying increasing magnitudes of pulling force to pull the T-bar structures 110 apart, thereby breaking the adhesive bond within the bonding area 134 as the T-bar structures 110A, 110B separate from each other. In the exemplary test data shown herein, The 5969 is equipped with a 1 kilonewton (kN) load cell and is set to a displacement speed of 12 mm / min. Figures 1 to 4 As shown, for each sample prepared, the maximum pull-off force during the separation of the T-bar structures 110A, 110B using the test apparatus 100 was recorded. The maximum pull-off stress was calculated by dividing the maximum pull-off force by the surface area of ​​the bonding area 134 (e.g., 25.4 mm×25.4 mm). At least 5 measurements were performed for each sample described herein.

[0114] Figure 5The pull-off stress determined by the 6 samples evaluated is listed in the table shown, as well as the failure (i.e., adhesion failure, cohesive failure (COH) and thin layer cohesive failure (TIC)) mode of the adhesive. As used herein, adhesion failure is when the adhesive is cleanly debonded from one of the substrates, leaving no residue on the debonded surface of the substrate. The cohesive failure mode is a unique failure mode in the adhesive material, in which part of the adhesive material remains on both sides of the adhesive bond (e.g., on two substrates). The thin layer cohesive failure mode is represented by the fact that no obvious damage is found in the material, but a thin layer of the adhesive material is retained on one substrate, while most of the adhesive material (e.g., 90% by weight or more) remains on the other substrate.

[0115] In the first exemplary SC-1500 sample, the R:H ratio was 1:1. SC-1500 was applied at a thickness of about 1.0 mm to cover the entire bonding area 134 of the T-bar structures 110A, 110B. In the first exemplary SC-1500 specimen, it was determined that an average of 0.24 megapascals (MPa) of pressure (pull-off stress) was required to mechanically fail the adhesive and separate the T-bar structures 110A, 110B along the adhesive bond line.

[0116] In the second exemplary SC-1500 sample, only The resin (R) component of SC-1500 was applied at a thickness of about 1.0 mm to cover the entire bonding area 134 of the T-bar structures 110A, 110B. In the second exemplary SC-1500 specimen, it was determined that an average of 0.005 megapascals (MPa) of pressure (pull-off stress) was required to mechanically fail the adhesive and separate the T-bar structures 110A, 110B along the adhesive bond line. In the third exemplary SC-1500 specimen, only the adhesive was applied to the T-bar structures 110A, 110B. The hardener (R) component of SC-1500 was applied at a thickness of about 1.0 mm to cover the entire bonding area 134 of the T-bar structures 110A, 110B. In the third exemplary SC-1500 specimen, it was determined that an average of 0.003 megapascals (MPa) of pressure (pull-off stress) was required to mechanically fail the adhesive and separate the T-bar structures 110A, 110B along the adhesive bond line. It should be noted that it is impractical to use 100% R or 100% H as a thermal interface material (TIM) for a battery module cooling plate assembly because 100% R or 100% H will tend to diffuse, or be moved out of the bond line, thereby affecting thermal performance.

[0117] In the fourth exemplary SC-1500 sample, the R:H ratio of 1:1 SC-1500 was applied only within the first bonding area 130A of the bonding area 134 (e.g., within the perimeter of the bonding area 134) with a width of about 5 mm to 6 mm and a thickness of about 1.0 mm, while the second bonding area 130B (e.g., the remaining surface area of ​​the bonding area 134) was empty (e.g., filled with ambient air). In this fourth exemplary SC-1500 specimen, the pull-off stress was determined to be about 0.14 MPa on average, which was reduced by about 41.7% compared to the first exemplary SC-1500 specimen.

[0118] In the fifth exemplary SC-1500 sample, the R:H ratio of 1:1 SC-1500 is applied only within the first bonding area 130A of the bonding area 134 (e.g., within the perimeter of the bonding area 134) at a width of about 5 mm to 6 mm and a thickness of about 1.0 mm, and the R:H ratio of 2:1 is SC-1500 was also applied at a thickness of about 1.0 mm only within the second bonding region 130B (e.g., the remaining surface area of ​​the bonding region 134). In this fifth exemplary SC-1500 specimen, the pull-off stress was determined to be about 0.12 MPa on average, which is about 50% lower than the first exemplary SC-1500 specimen.

[0119] In the sixth exemplary SC-1500 sample, the R:H ratio of 1:1 SC-1500 is applied only within the first bonding area 130A of the bonding area 134 (e.g., within the perimeter of the bonding area 134) at a width of about 5 mm to 6 mm and a thickness of about 1.0 mm, and the R:H ratio of 1:2 is SC-1500 was also applied only in the second bonding area 130B (e.g., the remaining surface area of ​​the bonding area 134) with a thickness of about 1.0 mm. In this sixth exemplary SC-1500 sample, the pull-off stress was determined to be about 0.46 MPa on average. It is believed that the result that the sixth exemplary SC-1500 sample shows a higher pull-off stress than the first exemplary SC-1500 sample is due to the increase in the proportion of the hardener contained in the second bonding area 130B in the sixth exemplary SC-1500 sample (R:H ratio is 1:2), making the adhesive (OO85) in the second bonding area 130B in the sixth exemplary SC-1500 sample harder than the adhesive (R:H is 1:1, OO80) in the first bonding area 130A, which is different from the first or fifth exemplary SC-1500 samples.

[0120] FIG. 6A to FIG. 6DAn image of the adhesive remaining on each T-bar structure 110A, 110B after the T-bar structures 110A, 110B have been forcibly separated (e.g., after they have been pulled apart with a pull-off force equal to or greater than that required to cause mechanical failure of the adhesive bond line). Fig. 6A As shown in Figure 4, the fourth specimen mainly exhibits a thin layer cohesive failure mode. Figure 6B As can be seen in FIG, the fifth specimen exhibits both thin layer cohesive failure and cohesive failure modes. It is believed that this combination of thin layer cohesive failure and cohesive failure modes results from the adhesive in the second bonding area 130B not being fully cured and at least partially remaining as a viscous fluid, at least in part due to its 2:1 R:H ratio. Figure 6C It can be seen that the sixth specimen mainly exhibits a thin layer cohesive failure mode, which is roughly similar to Fig. 6A The failure mode shown in Fig.6D It can be seen that the first exemplary SC-1500 specimen mainly exhibits a thin layer cohesive failure mode, which is generally similar to Fig. 6A and Figure 6C Failure modes are shown for the fourth and sixth exemplary SC-1500 specimens, respectively.

[0121] Certain "soft" adhesive gap fillers, particularly lightly cross-linked or uncross-linked adhesive gap fillers, have a tendency to squeeze out of the edges of the adhesive bond line between the T-bar structures 110A, 110B during thermal cycling. This is known as "pumping out" and is a common feature of heat sources (such as those found in electric vehicles or other items) and can be caused by changes in ambient temperature, changes in heat generation due to utilization of the heat source, etc. Therefore, the potential for "pumping out" in the methods disclosed herein was evaluated in a thermal cycling apparatus, generally designated 400, as shown. Figure 7 and Figure 8 As shown, according to the fifth sample, the arrangement and application of adhesives with different R:H ratios are used in the first bonding area 130A and the second bonding area 130B. Therefore, the first bonding area 130A uses an adhesive with an R:H ratio of 1:1. SC-1500 is filled, and the second bonding area 130B is substantially completely filled with a 2:1 R:H ratio of SC-1500. Adhesive is deposited in the first bonding area and the second bonding area on the top of the test plate 420, and the heating plate 410 is attached to the test plate 420 using fasteners 430 in a manner that produces a uniform and consistent adhesive bond layer between the test plate 420 and the heating plate 410 (e.g., using spacers). The heating plate has fluid channels (e.g., pipes made of a thermally conductive metal, such as copper) embedded therein to allow fluid to pass therethrough to provide substantially isothermal heating to the bonding area between the test plate 420 and the heating plate 410. Prior to commencing the thermal cycling test, the thermal cycling apparatus 100 is exposed to a curing temperature of 100° C. for at least 1 hour to cure the first adhesive and the second adhesive between the test plate 420 and the heating plate 410 of the thermal cycling apparatus 400. In the illustrated thermal cycling apparatus 400, the test plate 420 and the heating plate 410 are composed of Figure 7 and Figure 8 The thermal cycler 400 is shown as being made of materials having different thermal conductivities of steel and aluminum. The thermal cycler 400 is subjected to 1000 cycles from -40°C to 80°C, with a dwell time of 15 minutes at each temperature, after which the test plate 420 is separated from the heating plate 410 to inspect the adhesive bonding layer, generally designated as 440, wherein the uncured and / or partially cured second adhesive remains enclosed in the first bonding area, as shown in FIG. Figure 8 Unlike known conventional thermally conductive greases, no pumping of adhesive is observed in thermal cycling apparatus 400 because the adhesive applied to bonding area 134 is substantially unchanged after thermal cycling, at least compared to the adhesive applied to bonding area 134 before thermal cycling testing. Test plate 420 and heating plate 410 are separated, and it is observed that uncured or partially cured samples remain in the second bonding area, enclosed in the cured adhesive in the first bonding area.

[0122] A commercially available two-component, 2.0 W / mK thermally conductive urethane gap filler ( Another set of exemplary samples was prepared using UR-2002, available from LORD Corporation, which was formed by mixing a resin (R) component and a hardener (H) component according to a specified 1:1 R:H ratio. The urethane gap filler exemplary samples were prepared substantially similar to the silicone gap filler exemplary samples discussed above, which were Figure 1-8 In a first exemplary urethane sample of a urethane gap filler, both the first bonding area 130A and the second bonding area 130B are substantially completely filled with a 1:1 R:H ratio mixed with a thickness of about 1 mm. UR-2002. The first exemplary urethane specimen produced a pull-off stress of 0.25 MPa with a 95% confidence interval of 0.02 MPa and exhibited a cohesive bond failure mode. In the second exemplary urethane specimen, the first bonding area 130A was filled with a 1:1 R:H ratio mixed with a width of about 4 mm and a thickness of about 1 mm. UR-2002, such that the first bonding area 130A occupies approximately 30% of the total surface area and / or volume between the T-bar structures 110A, 110B on the bonding area 134. The second bonding area 130B is filled with a mixture of 2:1 R:H ratio and having a thickness of about 1 mm. UR-2002, so that the second bonding area 130B accounts for about 70% of the total surface area and / or volume between the T-bar structures 110A, 110B and on the bonding area 134. Because the urethane adhesive is applied in the first bonding area 130A and the second bonding area 130B with different R:H ratios, a variable crosslinking density and correspondingly variable strength from the outside to the inside of the bonding layer are generated, while still maintaining a high thermal conductivity bonding layer. The second exemplary urethane example produced a pull-off stress of 0.06MPa, with a 95% confidence interval of 0.02MPa, and exhibited a cohesive bonding layer failure mode. Therefore, the pull-off stress in the second exemplary urethane sample was reduced by about 75% compared to the first exemplary urethane sample.

[0123] According to another exemplary embodiment, a commercially available one-component, moisture-curing silicone sealant (GE5010) is applied in the first bonding area 130A to surround a one-component, non-reactive (thermoplastic), 3.9W / mK thermally conductive silicone grease applied in the second bonding area 130B. The silicone grease applied in the second bonding area 130B contains: by weight percentage, 13.22% vinyl-terminated PDMS (20 cst), a thermoplastic resin matrix; 1.95% hydroxyl-terminated PDMS (10,000 Da), a viscosity-reducing surfactant; 47.75% nearly spherical aluminum (about 10 microns in diameter), a thermally conductive filler; and 37.08% spherical zinc oxide (about 0.3 microns in diameter), a thermally conductive filler. The components of the above grease are mixed together at a speed of 1,200 rpm under vacuum using a Hauschild DAC-800 mixer for 1 minute. According to ISO22007-2, the thermal conductivity across the bonding layer was measured using a Hot Disk transient plane source (2500S model). In the first exemplary sealant sample, a single-component, moisture-curing silicone sealant was applied to the entire bonding area 134, substantially covering the entire first bonding area 130A and the second bonding area 130B with a thickness of approximately 1 mm. The first exemplary sealant sample produced a pull-off stress of 0.49 MPa, with a 95% confidence interval of 0.02 MPa, and exhibited a thin layer cohesive bonding layer failure mode. In the second exemplary sealant sample, the first bonding area 130A was filled with a single-component, moisture-curing silicone sealant with a width of approximately 4 mm and a thickness of approximately 1 mm, so that the first bonding area 130A occupied approximately 30% of the total surface area and / or volume on the bonding area 134 between the T-bar structures 110A, 110B. The second bonding area 130B is filled with a silicone grease having a composition mixed in the percentages just provided above, so that the second bonding area 130B accounts for about 70% of the total surface area and / or volume between the T-bar structures 110A, 110B and on the bonding area 134, and has a thickness of about 1 mm. The second exemplary sealant example produced a pull-off stress of 0.17 MPa, with a 95% confidence interval of 0.03 MPa, and exhibited a cohesive bonding layer failure mode. Therefore, the pull-off stress in the second exemplary sealant sample was reduced by about 65% compared to the first exemplary sealant sample, and most of the bonding area was thermally conductive and capable of heat transfer between adhesively connected surfaces. It should also be noted that since the width of the first bonding area 130A will remain unchanged as the size of the bonding area 134 increases, the proportion of the bonding area composed of the second bonding area 130B increases as the size of the bonding area 134 increases, thereby increasing the proportion of the thermally conductive bonding area.Furthermore, the failure mode of the second exemplary sealant specimen was primarily cohesive in nature, which is preferred from a heat transfer perspective.

[0124] According to yet another exemplary embodiment, a commercially available one-component, moisture-curing urethane sealant ( Another set of exemplary specimens was prepared by surrounding a one-component, non-reactive (thermoplastic), 3.7 W / mK thermally conductive urethane grease applied in the second bonding area 130B to form a gradient gap filler. The urethane grease applied in the second bonding area 130B includes: by weight percentage, 6.49% polypropylene glycol (MW 425 Daltons), a thermoplastic resin matrix; 0.96% phosphate polyester wetting agent, a viscosity reducing surfactant; 56.94% spherical alumina (average particle size or diameter of 70 microns), a thermally conductive filler; 35.24% spherical alumina (average particle size or diameter of 7 microns), a thermally conductive filler; and 0.37% polydimethylsiloxane-treated fumed silica, a rheological thixotropic additive. The constituent components of the above urethane grease were mixed together at 1,200 rpm under vacuum using a Hauschild DAC-800 mixer for 45 seconds. Thermal conductivity across the bonding layer was measured using a Hot Disk transient plane source (Model 2500S) in accordance with ISO 22007-2. In the first exemplary urethane sealant specimen, a single component, moisture-curing urethane sealant was applied to the entire bonding area 134 at a thickness of about 1 mm, substantially covering the entire first bonding area 130A and the second bonding area 130B. The pull-off stress generated by the first exemplary urethane sealant specimen exceeded about 0.6 MPa, which is the test limit of the test apparatus; therefore, a 95% confidence interval could not be determined, and the bonding layer failure mode could not be determined. In the second exemplary urethane sealant specimen, the first bonding area 130A was filled with a single component, moisture-curing urethane sealant having a width of about 4 mm and a thickness of about 1 mm, so that the first bonding area 130A occupied about 30% of the total surface area and / or volume on the bonding area 134 between the T-bar structures 110A, 110B. The second bonding area 130B is filled with a urethane grease having a composition mixed in the percentages provided just above, so that the second bonding area 130B occupies about 70% of the total surface area and / or volume between the T-bar structures 110A, 110B and on the bonding area 134, and has a thickness of about 1 mm. The second exemplary sealant example produced a pull-off stress of 0.14 MPa, a 95% confidence interval of 0.03 MPa, and exhibited a thin layer cohesive bonding layer failure mode. Therefore, in the second exemplary urethane sealant sample, the pull-off stress was reduced by at least more than 75%, at least 0.14 MPa, which is less than 25% of the maximum stress of 0.6 MPa that can be measured by the test device.Since the pull-off strength of the first exemplary urethane sealant embodiment can be significantly greater than 0.6 MPa, the reduction in pull-off strength of the second exemplary urethane sealant embodiment can be at least 80%, at least 90%, or even at least 95% compared to the first exemplary sealant specimen. In addition, unlike the first exemplary urethane sealant embodiment, in the second exemplary urethane sealant embodiment, a majority of the bond area is thermally conductive and capable of heat transfer between the adhesively connected surfaces.

[0125] In considering the data presented herein for each of the exemplary samples, it should be further noted that since the width of the first bonding area 130A will remain constant as the size of the bonding area 134 increases, as the size of the bonding area 134 increases, the percentage of the bonding area comprised of the second bonding area 130B also increases, thereby increasing the percentage of the bonding area that is thermally conductive. By using a 12 inch length and a 6 inch width and by applying a two-component, 3.8 W / mK thermally conductive silicone gap filling adhesive ( Instead of using T-bar structures 110A, 110B having a 1 inch x 1 inch bonding area 134, an example of this configuration was evaluated in which a bonding structure having a desired thickness (e.g., 1.0 mm) was bonded together using a T-bar structure 110A, 110B having a 1 inch x 1 inch bonding area 134 with an adhesive tape SC-1500) applied within a volume defined by the space on the bonding area.

[0126] In the first exemplary scaled sample, the SC-1500 adhesive was applied over the entire surface of the bonding area and the adhesive between the bonded structures was compressed to a desired thickness of about 1 mm, as described in the exemplary methods disclosed herein. The adhesive in the bonding area according to the first exemplary scaled sample was mixed to have an R:H ratio of 1:1. Thus, in the first exemplary scaled sample of the silicone gap filler, both the first bonding area and the second bonding area were substantially completely filled with a 1:1 R:H ratio mixed and having a thickness of about 1 mm. SC-1500 was filled. The first exemplary scaled specimen produced a pull-off stress of 0.18 MPa and exhibited a cohesive bond failure mode. In the second exemplary scaled specimen, the first bonding area was filled with a 1:1 R:H ratio of about 5 mm in width and about 1 mm in thickness. SC-1500, such that the first bonding area occupies about 20% of the total surface area of ​​the bonding area. The second bonding area is filled with a mixture of 2:1 R:H ratio and having a thickness of about 1 mm. SC-1500 is used to make the second bonding area account for about 80% of the total surface area of ​​the bonding area. Since SC-1500 is applied with different R:H ratios in the first bonding area and the second bonding area, a variable crosslinking density from the outside to the inside of the bonding layer and a correspondingly variable strength are generated, while still maintaining a high thermal conductivity bonding layer. The second exemplary scaled sample produced a pull-off stress of 0.03MPa and exhibited a cohesive bonding layer failure mode. Therefore, compared with the first exemplary scaled sample, the pull-off stress in the second exemplary scaled sample was reduced by about 83%.

Claims

1. A method for adhesively bonding a first substrate to a second substrate to reduce pull-off stress during separation of the first substrate and the second substrate, the method comprising: applying a first adhesive to a first bonding zone of the bonding area of ​​the first substrate; applying a second adhesive to a second bonding region of the bonding area of ​​the first substrate, the second adhesive having a bonding strength lower than the bonding strength of the first adhesive; pressing the first substrate against the second substrate; as well as forming an adhesive bonding layer including the first adhesive and the second adhesive between the first substrate and the second substrate; in: The first substrate comprises a heat source and the second substrate comprises a heat dissipation component; or The second substrate includes a heat source and the first substrate includes a heat dissipation component.

2. The method according to claim 1, wherein: The first bonding region of the bonding area is a perimeter of the bonding area; and The second bonding area of ​​the bonding region is located within and bounded by a perimeter formed by the first bonding area such that the second adhesive at least partially fills a volume within the perimeter. 3 . The method of claim 2 , wherein in the second bonding region, the second adhesive completely fills a volume between the first substrate and the second substrate. 4 . The method of claim 2 , wherein the first adhesive forms a continuous and uninterrupted layer around the perimeter of the bonding area.

5. The method according to claim 1, wherein: The second bonding area of ​​the bonding area is the perimeter of the bonding area; and The first bonding area of ​​the bonding region is located within and bounded by a perimeter formed by the second bonding area such that the first adhesive at least partially fills a volume within the perimeter. 6 . The method of claim 5 , wherein in the first bonding region, the first adhesive completely fills a volume between the first substrate and the second substrate.

7. The method of claim 5, wherein the second adhesive forms a continuous and uninterrupted layer around the perimeter of the bonding area.

8. The method according to claim 1, wherein: The first adhesive and the second adhesive comprise the same two-component adhesive formulation; and The first adhesive has an R:H ratio (resin to hardener) that is different from the R:H ratio of the second adhesive. 9 . The method of claim 8 , wherein a degree of crosslinking of the first binder is greater than a degree of crosslinking of the second binder.

10. The method of claim 9, wherein the second adhesive comprises an uncrosslinked material.

11. The method of claim 9, wherein the greater degree of crosslinking is due to a different R:H ratio of the first binder and the second binder.

12. The method of claim 8, wherein the R:H ratio of the first adhesive includes a relatively greater proportion of hardener than the R:H ratio of the second adhesive, and the R:H ratio of the second adhesive includes a relatively greater proportion of resin than the R:H ratio of the first adhesive.

13. The method of claim 1, wherein at least one of the first adhesive and the second adhesive comprises at least one of a urethane, silicone, acrylic, and epoxy-based material.

14. The method of claim 1, wherein the heat source comprises a battery module and / or the heat dissipation component comprises a cooling plate.

15. The method of claim 1, wherein the heat source comprises a battery module configured to provide power to an electric vehicle.

16. The method of claim 1, wherein the heat source comprises a microprocessor and the heat dissipation component comprises a cover and / or a heat sink.

17. The method of claim 1, wherein at least one of the first adhesive and the second adhesive comprises a thermally conductive filling resin composition.

18. The method of claim 1, wherein at least one of the first adhesive and the second adhesive comprises a thermally conductive gap-filling adhesive.

19. The method of claim 1, comprising separating the first substrate from the second substrate by breaking an adhesive bonding layer formed by the first adhesive and the second adhesive, wherein: Since the adhesive strength of the second adhesive is relatively low, the pull-off stress required to separate the first substrate and the second substrate is smaller than the pull-off stress required to separate the first substrate and the second substrate when the entire bonding area is covered by the first adhesive.

20. The method of claim 19, wherein the adhesive strength of the first adhesive and the second adhesive is related to a pull-off stress required to separate the first substrate from the second substrate.

21. The method of claim 1, comprising irradiating at least a portion of the first adhesive with a light source comprising ultraviolet (UV) light to depolymerize at least a portion of the first adhesive exposed to the light source, such that the bonding strength of the first adhesive is reduced relative to the bonding strength of the first adhesive before exposure to the light source.

22. The method according to claim 1, comprising: After the first adhesive and / or the second adhesive have been cured, the first adhesive and the second adhesive are exposed to a temperature above a predetermined softening temperature to reduce the adhesive strength of at least the first adhesive, wherein one of the first substrate and the second substrate includes a heat source, and wherein the softening temperature is within an operating temperature range of the heat source.

23. A system for adhesively bonding a first substrate to a second substrate to reduce pull-off stress during separation of the first substrate and the second substrate, the system comprising: a first adhesive applied to a first bonding zone of the bonding area of ​​the first substrate; and a second adhesive applied to a second bonding area of ​​the bonding region of the first substrate, the bonding strength of the second adhesive being lower than the bonding strength of the first adhesive; wherein the system is configured such that the first and second substrates are pressed against each other to form an adhesive bonding layer, the adhesive bonding layer comprising the first adhesive and the second adhesive between the first and second substrates; and in: The first substrate comprises a heat source and the second substrate comprises a heat dissipation component; or The second substrate includes a heat source and the first substrate includes a heat dissipation component.

24. The system of claim 23, wherein: The first bonding region of the bonding area is a perimeter of the bonding area; and The second bonding area of ​​the bonding region is located within and bounded by a perimeter formed by the first bonding area such that the second adhesive at least partially fills a volume within the perimeter.

25. The system of claim 24, wherein in the second bonding region, the second adhesive completely fills a volume between the first substrate and the second substrate.

26. The system of claim 24, wherein the first adhesive forms a continuous and uninterrupted layer around the perimeter of the bonding area.

27. The system of claim 23, wherein: The second bonding area of ​​the bonding area is the perimeter of the bonding area; and The first bonding area of ​​the bonding region is located within and bounded by a perimeter formed by the second bonding area such that the first adhesive at least partially fills a volume within the perimeter.

28. The system of claim 27, wherein in the first bonding region, the first adhesive completely fills a volume between the first substrate and the second substrate.

29. The system of claim 27, wherein the second adhesive forms a continuous and uninterrupted layer around the perimeter of the bonding area.

30. The system of claim 23, wherein: The first adhesive and the second adhesive comprise the same two-component adhesive formulation; and The first adhesive has an R:H ratio (resin to hardener) that is different from the R:H ratio of the second adhesive.

31. The system of claim 30, wherein the first adhesive has a greater degree of crosslinking than the second adhesive.

32. The system of claim 31, wherein the second adhesive comprises an uncrosslinked material.

33. The system of claim 31 , wherein the greater degree of crosslinking is due to a different R:H ratio of the first binder and the second binder.

34. The system of claim 30, wherein the R:H ratio of the first adhesive includes a relatively greater proportion of hardener than the R:H ratio of the second adhesive, and the R:H ratio of the second adhesive includes a relatively greater proportion of resin than the R:H ratio of the first adhesive.

35. The system of claim 23, wherein at least one of the first adhesive and the second adhesive comprises at least one of a urethane, silicone, acrylic, and epoxy based material.

36. The system of claim 23, wherein the heat source comprises a battery module and / or the heat dissipation component comprises a cooling plate.

37. The system of claim 23, wherein the heat source comprises a battery module configured to provide power to an electric vehicle.

38. The system of claim 23, wherein the heat source comprises a microprocessor and the heat dissipation component comprises a cover and / or a heat sink.

39. The system of claim 23, wherein at least one of the first adhesive and the second adhesive comprises a thermally conductive filler resin composition.

40. The system of claim 23, wherein at least one of the first adhesive and the second adhesive comprises a thermally conductive gap-filling adhesive.

41. The system of claim 23, wherein: The system is configured to separate the first substrate from the second substrate by breaking an adhesive bonding layer formed by the first adhesive and the second adhesive; and Since the adhesive strength of the second adhesive is relatively low, the pull-off stress required to separate the first substrate and the second substrate is smaller than the pull-off stress required to separate the first substrate and the second substrate when the entire bonding area is covered by the first adhesive.

42. The system of claim 23, wherein the adhesive strength of the first adhesive and the second adhesive is related to a pull-off stress required to separate the first substrate from the second substrate.

43. A system according to claim 23, wherein at least a portion of the first adhesive is configured such that, when at least a portion of the first adhesive is irradiated with a light source including ultraviolet (UV) light to depolymerize at least a portion of the first adhesive exposed to the light source, the bonding strength of the first adhesive is reduced relative to the bonding strength of the first adhesive before exposure to the light source.

44. The system of claim 23, wherein: The system is configured to, after the first adhesive and / or the second adhesive has been cured, reduce the adhesive strength of at least the first adhesive when exposed to a temperature above a predetermined softening temperature; One of the first substrate and the second substrate includes a heat source; and The softening temperature is within the operating temperature range of the heat source.

45. The system of claim 23, wherein the adhesive bonding layer has a lower adhesive strength than an adhesive bonding layer formed entirely of only the first adhesive or only of the second adhesive.

46. ​​The system of claim 45, wherein the first adhesive and the second adhesive at least partially mix together when the first substrate is pressed against the second substrate.

47. The system of claim 45, wherein: The system is configured to: separate the first substrate from the second substrate by destroying an adhesive bonding layer formed by the first adhesive and the second adhesive; and Since the bonding strength of the adhesive bonding layer is lower than the bonding strength of the adhesive bonding layer formed entirely only by the first adhesive or only by the second adhesive, the pull-off stress required to separate the first substrate and the second substrate is less than the pull-off stress required to separate the first substrate and the second substrate if the entire bonding area is covered only by the first adhesive or only by the second adhesive.

48. A system for adhesively bonding a first substrate to a second substrate to reduce pull-off stress during separation of the first substrate and the second substrate, the system comprising: a first adhesive applied to a first bonding zone on the bonding area of ​​the first substrate; and a second adhesive applied to a second bonding area on the bonding area of ​​the first substrate, the second adhesive having a bonding strength lower than the bonding strength of the first adhesive; wherein the system is configured such that the first substrate and the second substrate are pressed against each other to form an adhesive bonding layer including the first adhesive and the second adhesive between the first substrate and the second substrate; wherein one of the first substrate and the second substrate comprises a heat source; wherein the system is configured to reduce the bond strength of at least the first adhesive when exposed to a temperature above a predetermined softening temperature after the first adhesive and / or the second adhesive has been cured; and The softening temperature is within the operating temperature range of the heat source.

Citation Information

Patent Citations

  • Releasable substrate on carrier

    CN104838485A

  • Adhesives to replace ink step bezels in electronic devices

    CN107109140A

  • Adhesive sheet

    JP2003313520A

  • Substrate bonding method and inkjet head, and image forming apparatus

    JP2010184434A

  • Method for manufacturing an adhesive bond or composite and adhesive or matrix material suitable for this purpose

    US20140045964A1